Arahan Pengembangan Permukiman Baru Pasca Bencana Alam di Kota Palu (Studi Kasus: Kecamatan Mantikulore) - Febriansyah, Arie; Syafri; Rasyidi, Emil Salim; Asrib, Arista (Fakultas Teknik Universitas Bosowa, 2023)
Abstract. The goal of this study is to assess the carrying capacity and settlement capacity in the mantikulore district and to provide guidelines for the creation of new communities there following natural disasters. The carrying capacity analysis tool and settlement capacity are used in this quantitative research approach to analyze the carrying capacity and capacity of settlements in the Mantikulore sub-district, and new settlement development directions are developed after natural disasters in the Mantikulore district using qualitative descriptive analysis. Mantikulore district continues to be unable to support and accommodate settlements, according to the findings of the analysis of carrying capacity and settlement capacity. Based on the findings of the investigation of the carrying capacity and capacity of settlements with disasters in the Mantikulore district, the path of settlement development is separated into numerous zones. The direction of settlement growth in terms of things like zoning seismically vulnerable areas and land use laws, warnings about potential disaster impacts to the community, schoolchildren, and the media, and suggestions for relocation.